MENINGKATKAN HASIL BELAJAR SISWA DALAM MATERI TEOREMA PYTHAGORAS MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU PICTURE PUZZLE DI KELAS VIII - Olinggahe, Septiniarti; -, Majid; Irfah, Auli (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
This study aims to improve student learning outcomes through the Problem Based Learning learning model assisted by Picture Puzzle on the Pythagorean theorem material in class VIII of SMP Negeri 3 Satap Tibawa. The subjects in this study were all students of class VIII of SMP Negeri 3 Satap Tibawa totaling 18 students, namely 6 male students and 12 female students. The method used in this study is Classroom Action Research (CAR) which is divided into several stages, namely, the preparation stage, the implementation stage, the monitoring and evaluation stage, the analysis and reflection stage. The observation data in cycle I on teacher and student activities only achieved an average assessment of quite good and this has not met the completion criteria, namely at least good or very good, and the level of completion of student learning outcomes in cycle I who reached the KKM value was only 7 people or 38.89% while there were 11 students who had not completed it or classically 61.11%. Because the indicator of success in completing the student learning test has not been achieved, namely at least 75%, the research was continued to cycle II. In cycle II, the results of observations of teacher and student activities have reached an average assessment of very good, this shows that teacher and student activities have met the completion criteria, namely at least good or very good, and for student learning outcomes there are 15 students who have achieved the KKM score or classically 83.33%. From this statement, it can be concluded that the Problem Based Learning learning model assisted by Picture Puzzle is able to improve student learning outcomes. Keywords: Improve, Problem Based Learning Assisted by Picture Puzzle, Mathematics Learning Outcomes, Pythagorean Theorem